Pengaruh Kualitas Produk Dan Promosi Terhadap Minat Beli Kendaraan Listrik (Motor Dan Sepeda) Di PT Cipta Jalan Nusantara Kota Tangerang Selatan - Ronaldo Laurent; Aldila Rahma Putri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of product quality and promotion on purchasing interest in electric vehicles (motorcycles and bicycles) at PT Cipta Jalan Nusantara, South Tangerang City. The research method uses a quantitative approach with an associative method. The sampling technique used is Probability Sampling, a sampling method using the slovin technique. Data analysis includes instrument testing (validity and reliability), classical assumption tests (normality, multicollinearity, and heteroscedasticity), linear regression, correlation coefficient, coefficient of determination, and hypothesis testing (t test and F test). The results of the analysis show that the coefficient of determination is 0.504, which means that product quality and promotion simultaneously contribute to purchasing interest by 50.4%, while the remaining 49.6% is influenced by other factors outside this study. The results of the t test show that product quality has a positive and significant influence on purchasing interest, the calculated t value > t table (9.969 > 0.676) with a significance value of 0.000 < 0.05. Promotion has a positive and significant influence on customer satisfaction with a calculated t_value > t_table (12.509 > 0.676) with a significance value of 0.000 < 0.05. Meanwhile, the results of the F test show that simultaneously product quality and promotion have a positive and significant influence on purchasing interest with a calculated F_value > F_table, namely (85.325 > 3.05) with a significance value of 0.000 < 0.05.